UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM MENGATASI MASALAH BELAJAR SISWA - Zahroh, Zulfa Aminatuz; Anwar, Ahmad (https://www.ejournal.smaamc.sch.id/index.php/belajar, 2023)
Student learning problems refer to the challenges students face in receiving or absorbing lessons at school. The learning process for each student does not always run smoothly; sometimes students can quickly grasp the material, while at other times they encounter difficulties. This phenomenon is often observed among learners. The research employs a descriptive qualitative approach, with data sources obtained through observation, interviews, and documentation. The aim of this paper is to help teachers address student learning difficulties in the learning process. The findings of this study are: The efforts of teachers to overcome student learning difficulties in Islamic Religious Education subjects play a very important role. Islamic Education teachers must understand and master strategies to address student learning difficulties. Teachers need to pay attention to the difficulties experienced by each student so that the learning process can achieve its goals effectively and efficiently. One strategy that teachers can implement is directing students to read books in the library related to Islamic Religious Education. Additionally, teachers should be willing to review material that students have not yet understood. Students need to be active in following all the lessons delivered by teachers at school and be diligent in asking teachers questions if there is something they do not understand from the explanations given.